# Chapter 9 - Section 9.3 - Solving Pairs of Linear Equations by Substitution - Exercises - Page 334: 24

$(-2,-3)$

#### Work Step by Step

To solve the following pair of linear equations, we will use the substitution method. $x+6y=-20$ $5x-8y=14$ We solve the first equation for $x$. So, $x+6y=-20$ $x=-6y-20$ First, we substitute the $-6y-20$ for $x$ in the second equation. $5x-8y=14$ $5(-6y-20)-8y=14$ $\rightarrow$ Simplify $-30y-100-8y=14$ $-38y=100+14$ $-38y=114$ $\rightarrow$ Solving for $y$ $y=\frac{114}{-38}$ $y=-3$ Now we substitute $-3$ for $y$ in any of the equations to solve for $x$. $x=-6y-20$ $x=-6(-3)-20$ $x=18-20$ $x=-2$ The apparent solution is $(-2,-3)$. To check, we substitute $x=-2$ and $y=-3$ in any of the equations to see if the statement is true or false. If it is true, our solutions are correct. If it is false, the system of equations has no solution. So, $5x-8y=14$ $5(-2)-8(-3)=14$ $-10+24=14$ $14=14$ $\rightarrow$ true Thus, the solution is $(-2,-3)$.

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.